2001
DOI: 10.1074/jbc.m102754200
|View full text |Cite
|
Sign up to set email alerts
|

Cooperative Regulation of the Invasive and Metastatic Phenotypes by Different Domains of the Type I Insulin-like Growth Factor Receptor β Subunit

Abstract: The receptor for the type 1 insulin-like growth factor (IGF-I) regulates multiple cellular functions impacting on the metastatic phenotype of tumor cells, including cellular proliferation, anchorage-independent growth, survival, migration, synthesis of the 72-kDa type IV collagenase and invasion. We have used site-directed mutagenesis to generate domain-specific mutants of the receptor ␤ subunit to analyze the role of specific tyrosines in the regulation of the invasive/metastatic phenotype. Poorly invasive M-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
84
0
1

Year Published

2003
2003
2011
2011

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(93 citation statements)
references
References 48 publications
8
84
0
1
Order By: Relevance
“…Previous mutational analysis studies have shown that signals derived from both regions of the IGF1R cooperate to enhance tumor metastasis. 15 Moreover, a relationship between local recurrence and radioresistance due to mutations at the C-terminal domain 43 could not be confirmed in our former study. 30 So far, no other previous investigators have analyzed the importance of IGF1R mRNA levels or IGF1R mutation status on breast carcinoma subtypes for a comparison with our data.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…Previous mutational analysis studies have shown that signals derived from both regions of the IGF1R cooperate to enhance tumor metastasis. 15 Moreover, a relationship between local recurrence and radioresistance due to mutations at the C-terminal domain 43 could not be confirmed in our former study. 30 So far, no other previous investigators have analyzed the importance of IGF1R mRNA levels or IGF1R mutation status on breast carcinoma subtypes for a comparison with our data.…”
Section: Discussionmentioning
confidence: 55%
“…[9][10][11][12] Recent epidemiological and clinico-pathological data have supported the role of the insulin-like growth factor-1 (IGF1R) signaling system on tumor development and progression. [13][14][15][16][17] In breast carcinoma, high levels of IGF1R have been detected in 30-82%, 18,19 but its prognostic value is controversial. [20][21][22][23][24][25][26][27] Emerging experimental and clinical data suggest that the IGF1R and ER/PR pathways are interactive.…”
mentioning
confidence: 99%
“…Previously, we identified the IGF-IR as a key regulator of the liver-metastasizing phenotype in a Lewis lung carcinoma-based model of organ site-specific metastasis (Brodt et al, 2001;Samani et al, 2004). The present study was prompted by our finding, based on gene chip microarray analysis, that in this model, the acquisition of a liver-metastasizing phenotype was associated with markedly increased type IV collagen a1 and a2 expression levels.…”
Section: Introductionmentioning
confidence: 80%
“…Identification of genes differentially expressed in IGF-IR-overexpressing tumor cells that acquired a liver-metastasizing potential Previously, we reported that lung-metastasizing M-27 cells that were stably transfected with a full-length hIGF-IR complementary (c)DNA (M-27 IGFÀIR ) acquired a liver-colonizing potential (Brodt et al, 2001). We show here that the increase in their liver-colonizing potential, as seen following intrasplenic injection of the cells (representative histology shown in Figure 1a), was associated with major changes to gene expression in these cells, as revealed by Affymetrix gene chip analysis and depicted in the heat map shown in Figure 1b (with full list shown in Supplementary Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…dnIGF-1R isoforms with deletions in the cytoplasmic tyrosine kinase domain such as dnIGF-1R 950 and dnIGF-1R 952 Min et al, 2003Min et al, , 2005 and also secreted isoforms like dnIGF-1R 486 and dnIGF-1R 482 (Reiss et al, 1998(Reiss et al, , 2001Min et al, 2003) mediate antineoplastic effects based on the induction of tumor cell apoptosis and growth inhibition. Moreover, specific mutations in the important carboxy-terminal domain (Tyr1250 and Tyr1251) and the tyrosine kinase domain (Tyr1131, Tyr1135 and Tyr1136) reduce proliferation, tumor cell survival and migration (Gronborg et al, 1993;Baserga et al, 1997;Brodt et al, 2001). Several investigators also employed antisense RNA and antisense oligodeoxynucleotide techniques to block IGF-1R synthesis (Trojan et al, 1993;Resnicoff et al, 1994Resnicoff et al, , 1995Lafarge-Frayssinet et al, 1997), leading to increased apoptosis and reduced proliferation.…”
Section: Other Approachesmentioning
confidence: 99%